2021
DOI: 10.1002/ijgo.13963
|View full text |Cite
|
Sign up to set email alerts
|

“Suction Tube Uterine Tamponade” for treatment of refractory postpartum hemorrhage: Internal feasibility and acceptability pilot of a randomized clinical trial

Abstract: Objective: To assess feasibility and acceptability of a novel, low-cost "Suction Tube Uterine Tamponade" (STUT) treatment for refractory postpartum hemorrhage (PPH). Methods:We allocated patients with refractory PPH by randomly ordered envelopes to STUT or routine uterine balloon tamponade (UBT, Ellavi free-flow system) in 10 hospitals in South Africa. In the STUT group, a 24FG Levin stomach tube was inserted into the uterine cavity and vacuum created with a vacuum pump or manual vacuum aspiration syringe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Celox and the modified Bakri had no available published studies conducted in an LMIC setting, and only the Levin gastric tube had a reported randomised controlled trial in process. 24 There was no standardised primary outcome in the 14 studies reviewed.…”
Section: Bmj Public Healthmentioning
confidence: 99%
“…Celox and the modified Bakri had no available published studies conducted in an LMIC setting, and only the Levin gastric tube had a reported randomised controlled trial in process. 24 There was no standardised primary outcome in the 14 studies reviewed.…”
Section: Bmj Public Healthmentioning
confidence: 99%
“…Improvised use of a Bakri balloon catheter as a suction catheter is in routine use at the University Hospital, Zurich, Switzerland [ 40 ]. Use of an inexpensive Levin stomach tube FG 24 to 36 for ‘suction tube uterine tamponade’ has been reported [ 41 , 42 ].…”
Section: Uterine Suction Tamponadementioning
confidence: 99%
“…Another approach to generate intrauterine vacuum tamponade involves using a Levin stomach tube (FG24 or FG36), which has an open end and 4 side ports near the open tip. [12][13][14] The Levin stomach tube is low cost and has many favorable design features, including a rounded tip, wide-bore, and circumferentially placed side ports. The FG36 Levin stomach tube is 12 mm in diameter and has 10 mm side ports.…”
Section: Novel Approaches To Generating An Intrauterine Vacuum To Tre...mentioning
confidence: 99%